2021
DOI: 10.21203/rs.3.rs-402978/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The efficacy of first-line ART regimens based on RPV in HIV-infected patients with pre-existing E138A mutation in reverse transcriptase

Abstract: Introduction It was previously shown that the presence of the E138A mutation is associated with resistance to rilpivirine (RPV). Detection of this mutation is considered as contraindication for RPV use within the first-line ART. It is a lack of knowledge regarding efficacy of first-line RPV-based ART in patients bearing HIV with E138A mutation. In absence of HIV genotyping in naïve patients it may influence the clinical decisions.Methods We have collected all available patients unconventionally treated with RP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Over half (58.2%) of PWID in our study harbored E138A, conferring low-level resistance to the NNRTIs etravirine and rilpivirine (48,49). Other studies have observed E138A among people living with HIV in Pakistan, reporting varying prevalence in ART-experienced (13-78%)…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Over half (58.2%) of PWID in our study harbored E138A, conferring low-level resistance to the NNRTIs etravirine and rilpivirine (48,49). Other studies have observed E138A among people living with HIV in Pakistan, reporting varying prevalence in ART-experienced (13-78%)…”
Section: Discussionmentioning
confidence: 55%
“…NRTIs: K219R confers resistance to azidothymidine (41,42); and S68G is associated with K65R mutants to improve viral replication (43). NNRTIs: K101E confers highly-reduced susceptibility to nevirapine and decreases efavirenz, etravirine, and rilpivirine susceptibility (44); K103N is associated with resistance to nevirapine and efavirenz (45,46); V106I confers potential low-level resistance to doravirine, etravirine, nevirapine, and rilpivirine (47); E138A and E138Q confer reduced susceptibility to etravirine and reduced, potentially full, susceptibility to rilpivirine (48,49); V179D is associated with low-level resistance to efavirenz, nevirapine, etravirine, and rilpivirine (50); V179T has been reported with reduced susceptibility to etravirine in the presence of other DRMs (51); V179I is associated with resistance to etravirine and rilpivirine (52); and Y188H has been reported to confer resistance to nevirapine and efavirenz (53).…”
Section: Analysis Of Hiv Drug Resistance Analysismentioning
confidence: 99%